2019
DOI: 10.1002/psp4.12378
|View full text |Cite
|
Sign up to set email alerts
|

A General Framework for Assessing In vitro/In vivo Correlation as a Tool for Maximizing the Benefit‐Risk Ratio of a Treatment Using a Convolution‐Based Modeling Approach

Abstract: The net benefit of a treatment can be defined by the relationship between clinical improvement and risk of adverse events: the benefit‐risk ratio. The optimization of the benefit‐risk ratio can be achieved by identifying the most adequate dose (and/or dosage regimen) jointly with the best‐performing in vivo release properties of a drug. A general in silico tool is presented for identifying the dose, the in vitro and the in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Unfortunately, there is no single pharmacokinetic parameter that can describe this complex process. That said, recent pharmacokinetic-pharmacodynamic modeling using data for several ER MPH formulations has attempted to characterize the optimal drug release characteristics needed for optimal clinical benefit (discussed further in Section 7) [111,120].…”
Section: Pharmacokinetic Profile and The Resulting Pharmacokinetic-phmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is no single pharmacokinetic parameter that can describe this complex process. That said, recent pharmacokinetic-pharmacodynamic modeling using data for several ER MPH formulations has attempted to characterize the optimal drug release characteristics needed for optimal clinical benefit (discussed further in Section 7) [111,120].…”
Section: Pharmacokinetic Profile and The Resulting Pharmacokinetic-phmentioning
confidence: 99%
“…With OROS-MPH used as a reference drug, this modeling work by Gomeni and colleagues revealed that the optimal MPH release pattern for formulations exhibiting dual release characteristics is as follows: 1) approximately 20% of the dose released in the first process followed by the remainder of the dose in the second process; 2) a shorter time for delivering the initial fraction of the dose and a prolonged time for delivering the second fraction; and 3) a slower rate of release during both processes. Furthermore, an extension of this work proposed a convolution-based modeling approach to facilitate the development of drug formulations with optimal in vivo release properties by using in vivo-in vitro correlation (IVIVC) as a tool for maximizing the benefit-risk ratio of a treatment [120]. Specifically, a surface response analysis was used to identify the drug-related properties that could affect the clinical benefit of a treatment by connecting in vitro and in vivo drug release, in vivo drug release with pharmacokinetics, and pharmacokinetics with pharmacodynamics.…”
Section: Expert Opinionmentioning
confidence: 99%
“…20 Recently, a convolution-based modeling approach has been shown to represent a powerful and flexible tool for modeling complex pharmacokinetics of extended release (ER) and LAI products, and for maximizing the benefit-risk ratio of a treatment by optimizing the drug release properties using IVIVC and integrated PK/PD models. 21 Using this approach, the time course of the drug concentration can be described by convolving an input function with a disposition and elimination function when input and disposition functions are described by parametric models. A generalization of this method is now proposed for increasing the flexibility of the model and for providing an extended ability to characterize irregular drug release process.…”
Section: Introductionmentioning
confidence: 99%
“…Several pharmacokinetic strategies have been developed and applied to analyze such atypical absorption profiles, including the use of physiologically based pharmacokinetic approaches, 12 double or triple Weibull in vivo release models, 13,14 parallel zero‐order immediate release and, after a lag time, first‐order release, 15–17 transit compartments for delayed drug release, 18 combination of immediate first‐order release and transit compartments, 19 and inverse Gaussian density absorption 20 . Recently, a convolution‐based modeling approach was shown to represent a powerful and flexible tool for modeling complex pharmacokinetics of extended‐release and LAI products, and for maximizing the benefit‐risk ratio of a treatment by optimizing the drug release properties using IVIVC and integrated PK/pharmacodynamic models 21 …”
mentioning
confidence: 99%
“…In extending the concept of modeling, Roberto Gomeni (Pharmacometrica, France) discussed general in silico frameworks for maximizing the benefit-risk ratio of a treatment. The net benefit of a treatment is usually defined by the relationship between potential clinical improvement and the risk of adverse events (Gomeni et al, 2019). He introduced the concept of convolution-based modeling as a means of optimizing the potential clinical benefit of new pharmacological treatments.…”
Section: Introductionmentioning
confidence: 99%